Sumbangan Pemikiran Hak Asasi Manusia Terhadap Pembaharuan Kitab Undang-Undang Hukum Acara Pidana (KUHAP) - Wibowo, Ari (Unisia, 2018)
The idea of renewal of the Criminal Procedure Code can not be separated from the conceptual contribution of Human Rights (HAM). This contribution has been explicitly included in the preamble of the draft of Criminal Procedure Code. Although the current Criminal Procedure Code already provides protection to the rights of the suspect or the accused, but the implementation is still not optimal. Therefore, in the draft of Criminal Procedure Code there is a new institution called the Judicial Commissioner (Rechter-Commissaris) to replace the function of Pretrial institutions. The Judicial Commissioner has far wider powers of Pretrial institution, so that the protection of the rights of suspects or defendants in any stage of the judicial process will be more secure fulfillment. The development of human rights concept also contributed to the idea to regulate the rights of victims in the renewal of the Criminal Procedure Code. Protection of the rights of victims in the current Criminal Procedure Code is limited to the rights to the incorporation of lawsuits for damages to the criminal case. Because it has not adequately regulated in the current Criminal Procedure Code, the draft of Criminal Procedure Code regulates the rights of victims, both associated with involvement in all stages of judicial proceedings and the right to sue for damages.